2003
DOI: 10.1523/jneurosci.23-18-06982.2003
|View full text |Cite
|
Sign up to set email alerts
|

Multisensory Integration during Motor Planning

Abstract: When planning goal-directed reaches, subjects must estimate the position of the arm by integrating visual and proprioceptive signals from the sensory periphery. These integrated position estimates are required at two stages of motor planning: first to determine the desired movement vector, and second to transform the movement vector into a joint-based motor command. We quantified the contributions of each sensory modality to the position estimate formed at each planning stage. Subjects made reaches in a virtua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
320
3
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 360 publications
(342 citation statements)
references
References 44 publications
18
320
3
1
Order By: Relevance
“…A difference in reach acceleration under different sensory inputs could be related to increased uncertainty leading to less confident movement, characterised with less THE RUBBER HAND ILLUSION IN AUTISM SPECTRUM DISORDERS acceleration (Jeannerod, 1986;Rossetti et al, 1995;Kording & Wolpert, 2004;Sober & Sabes, 2003). Uncertainty can have multiple sources: uncertainty in prior assumptions, mismatch with expectations leading to prediction errors as movement unfolds, and lack of precision of sensory estimates (Bays & Wolpert, 2007).…”
Section: The Rubber Hand Illusion In Autism Spectrum Disorders 18mentioning
confidence: 99%
“…A difference in reach acceleration under different sensory inputs could be related to increased uncertainty leading to less confident movement, characterised with less THE RUBBER HAND ILLUSION IN AUTISM SPECTRUM DISORDERS acceleration (Jeannerod, 1986;Rossetti et al, 1995;Kording & Wolpert, 2004;Sober & Sabes, 2003). Uncertainty can have multiple sources: uncertainty in prior assumptions, mismatch with expectations leading to prediction errors as movement unfolds, and lack of precision of sensory estimates (Bays & Wolpert, 2007).…”
Section: The Rubber Hand Illusion In Autism Spectrum Disorders 18mentioning
confidence: 99%
“…However, Sober and Sabes(2003) found that the relative contributions of vision and proprioception are not fixed but variable depending on the computation being performed. Furthermore, even for the same computation, the brain weights differently depending on the context such as the content of the visual information or the sensory modality for the target location, suggesting that the brain tries to minimize errors arising from transformation between coordinates (Sober and Sabes, 2005).…”
Section: Relative Contributions Of Vision and Proprioceptionmentioning
confidence: 99%
“…However, a recent study challenged this view. Sober and Sabes (2003) considered a reaching task where state of the limb could be estimated using both vision and proprioception. They described two important psychophysical results: First, the estimate of limb state used for kinematic planning of a reach relied mostly on a representation of limb state in terms of vision.…”
mentioning
confidence: 99%
“…First, the design of those and many other experiments (Flanagan and Rao, 1995;Lateiner and Sainburg, 2003;Sober and Sabes, 2003) relied on conflict between visual and kinesthetic feedback about the hand. Because both information types were available simultaneously (to create conflict), a direct visual-visual or kinesthetic-kinesthetic target-hand comparison was always possible.…”
Section: Introductionmentioning
confidence: 99%